Sustainability and green IT education: Practice for incorporating in the Australian higher education curriculum - Issa, Tomayess; Issa, Theodora; Chang, Vanessa (Common Ground Publishing, 2014)
Due to the rapid increase in the use of Information and Communications Technology (ICT) by individuals and organizations around the world, ICT has become a significant instrument for searching, conducting research, communication, entertainment, and commerce and information, just to name a few activities. However, the recycling of ICT end-products is becoming a major dilemma for individuals and organizations. This is not simply a matter of being concerned about environmental damage or providing a solution to an environmental problem; it is a problem that should concern all of us. Indeed, a contemporary society should tackle and address such a problem and address it as a matter of urgency for the sake of the current and future stakeholders around the world. Stakeholders at all levels, including universities, must contribute to the transition towards a sustainable world. Universities play a major role in transforming societies’ and students’ critical philosophies and world views through their higher education and research. Universities need to raise the students’ awareness, especially in relation to their moral responsibility to contribute to sustainable development, and guide them to a better, sustainable future. This study discusses the development and delivery of a new Master unit dealing with the significance of sustainability and Green IT. This study provides empirical evidence based on quantitative and qualitative data from formal and informal feedback and reflections about the unit in general from 36 students. The students’ comments reflect their satisfaction with the unit’s overall constructs and assessments. The comprehensive outcomes confirm that students have become aware of what sustainable development is and how Green ICT should contribute to tackle this problem.